1978
DOI: 10.1176/appi.psychotherapy.1978.32.2.172
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Suicidal Behavior in the United States

Abstract: Suicidal behavior in the United States from 1900 to 1975 is reviewed. The data presented cover demographic variables such as: age, sex, color, and geographic area. While the overall suicide rate continues to increase, the most striking upturn can be seen in both sexes between the ages of 15 to 25 years. The need for a wide range of innovative approaches and increased research is manifest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(24 citation statements)
references
References 0 publications
3
21
0
Order By: Relevance
“…Several investigators have found that the relationship between age and changes in suicide rate depends on gender (8)(9)(10). For example, Frederick (9) found that suicide rates increased for both young males and females, but the increase for males was greater.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have found that the relationship between age and changes in suicide rate depends on gender (8)(9)(10). For example, Frederick (9) found that suicide rates increased for both young males and females, but the increase for males was greater.…”
mentioning
confidence: 99%
“…For example, Frederick (9) found that suicide rates increased for both young males and females, but the increase for males was greater. McIntosh & Jewel1 ( I l ) , in examining sex-related trends in suicide rates, found that the ratio of male to female suicides over time increased for the young and declined for the old.…”
mentioning
confidence: 99%
“…The frequency of depression in the elderly is indirectly demonstrated firstly by the high suicide rate of subjects over 70 years (Frederich 1978) and secondly by the prescription of antidepressant drugs, which shows a peak in elderly populations as reported by Grimmson (1977).…”
Section: Abstract: Trazodone -Mianserin Amitriptyline -Elderly -Majomentioning
confidence: 90%
“…Instances of taking a few pills and then immediately calling for help or superficially cutting the wrists are examples. A number of authors believe (Frederick, 1978;Miller, 1979, andFine, et al, 1980) that any type of life-threatening behavior or communication must be taken seriously.…”
Section: Identifying Suicide Potentialmentioning
confidence: 99%